Effective CO2 adsorption on pristine and chemically functionalized MWCNTs - Shukrullah, S. (American Institute of Physics Inc., 2016)
Carbon dioxide is one of the major greenhouse gases, which directly links to global warming. In this study, the laboratory produced multi-walled carbon nanotubes (MWCNTs) were amine-functionalized and tested for their potential as a CO2 adsorbent material. The CVD grown MWCNTs were treated with H2SO4/HNO3 and functionalized with 30 of 3-aminopropyltriethoxysilane (APTS). Both the pristine and functionalized MWCNTs were characterized for their surface morphology, chemical composition and functional groups by using FESEM, EDX and FTIR techniques. The acidic and APTS treatment to MWCNTs resulted in unbundling and loosening of the nanotubes from their bundled, agglomerated and entangled forms. Furthermore, oxidation and functionalization also significantly influenced the CO2 adsorption capacity of MWCNTs. The breakthrough curves (adsorption isotherms) revealed that the modified MWCNTs exhibit higher capacity for CO2 adsorption as compared to the pristine MWCNTs. Overall, CO2 uptake by the pristine and modified MWCNTs was found about 0.00025 mol/g and 0.00038 mol/g, respectively. Â© 2016 Author(s).